Evaluating the Research Funding Opportunities for Library & Information Science Professionals: an Evaluative Study - Kureshi P.S.L.; Upadhyay N.; Chakraborty K. (My University, 2025)
This research paper highlights the top twenty research funding agencies of the world in the discipline of Information Science and Library Information Science. The citation analysis method has been adopted for the present study and used the database Web of Science and InCites. The aim of this research paper is to make aware research scholars, faculty members, LIS professional and Practitioners, and policymakers about the various National and International top-level funding agencies available to fund their research proposals. The research and academic fraternity and particularly the library professionals who always face problems to get funds to work on any project will able to start new research with innovative ideas with the help of research grant. The finding of the study gives the insight of top-level research funding data with publication ratio of funded research publications in both Open and Closed access journals covered by WoS and InCites bibliographic Database. This paper also focused on the collaboration pattern of funded research publications. © 2021. All Rights Reserved